2007
DOI: 10.1158/1078-0432.ccr-06-2837
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Testing of Clinically Applicable Strategies for Overcoming Trastuzumab Resistance Caused by PTEN Deficiency

Abstract: Purpose: We have previously shown that PTEN loss confers trastuzumab resistance in ErbB2-overexpressing breast cancer using cell culture, xenograft models, and patient samples. This is a critical clinical problem because trastuzumab is used in a variety of therapeutic regimens, and at the current time, there are no established clinical strategies to overcome trastuzumab resistance. Here, we did preclinical studies on the efficacy of clinically applicable inhibitors of the Akt/ mammalian target of rapamycin (mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 30 publications
(34 reference statements)
5
129
0
Order By: Relevance
“…7 HER2+ breast cancers are treated with targeted drugs (trastuzumab, lapatinib) along with chemotherapy. Resistance to trastuzumab 8,9 has been found to be due to increased signaling through the PI3K/AKT pathway. Genetic alterations in the PI3K pathway are also implicated in reduced response to lapatinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…7 HER2+ breast cancers are treated with targeted drugs (trastuzumab, lapatinib) along with chemotherapy. Resistance to trastuzumab 8,9 has been found to be due to increased signaling through the PI3K/AKT pathway. Genetic alterations in the PI3K pathway are also implicated in reduced response to lapatinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Downstream signaling pathway members were proposed as potential source for trastuzumab resistance, including p27 Kip1, PTEN, PI3K, mTOR, and Akt. [17][18][19] Cross-talk with other signaling pathways including insulin-like growth factor receptor-1, ER pathway, and vascular endothelial growth factor that have the ability to bypass ERBB2 blockade have also been proposed to be involved in trastuzumab resistance. [20][21][22] However, these studies were all preclinical or in cell lines, and to date, there are no clinically validated markers to predict de novo or …”
Section: Discussionmentioning
confidence: 99%
“…Everolimus is an oral mTOR inhibitor blocking the PI3K pathway. Preclinical studies demonstrated that the combination of everolimus and trastuzumab rescued phosphatase and tensin homolog (PTEN) loss-induced trastuzumab resistance and slowed the growth of HER2+ breast cancer cells [Lu et al 2007]. Everolimus was evaluated as first-line therapy for HER2+ MBC in the BOLERO-1/TRIO 019 trial, that randomized 719 patients with treatment naïve HER2+ MBC in a 2:1 ratio to receive trastuzumab and paclitaxel in combination with everolimus (n = 480) or placebo (n = 239).…”
Section: Everolimusmentioning
confidence: 99%